2020
DOI: 10.3390/ijms21197016
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vesicle Trafficking Defects in the Pathogenesis of Prion and Prion-Like Disorders

Abstract: Prion diseases are fatal and transmissible neurodegenerative diseases in which the cellular form of the prion protein ‘PrPc’, misfolds into an infectious and aggregation prone isoform termed PrPSc, which is the primary component of prions. Many neurodegenerative diseases, like Alzheimer’s disease, Parkinson’s disease, and polyglutamine diseases, such as Huntington’s disease, are considered prion-like disorders because of the common characteristics in the propagation and spreading of misfolded proteins that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…A schematic representation of our study on how a loss in Rab7 activation can lead to elevated cholesterol levels is depicted in Figure 10 . Many neurodegenerative diseases present with similar impairments associated with vesicle trafficking and lysosomal maturation defects ( 36 ). In the case of prion infections, we have demonstrated that vesicular trafficking defects due to reduced Rab7 activation can result in elevated cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A schematic representation of our study on how a loss in Rab7 activation can lead to elevated cholesterol levels is depicted in Figure 10 . Many neurodegenerative diseases present with similar impairments associated with vesicle trafficking and lysosomal maturation defects ( 36 ). In the case of prion infections, we have demonstrated that vesicular trafficking defects due to reduced Rab7 activation can result in elevated cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…The retrograde LDL trafficking to the Golgi complex is also affected, potentially due to a reduced interaction of Rab7 with Vps 35. Adapted from ( 36 ). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…277 Given the prevalence of PrP c in lipid rafts at the plasma membrane, 278 Cu(II)-mediated PrP aggregates may also stimulate its endocytosis and vesicular trafficking at synapses, suggesting a potential role of PrP C in the uptake and efflux of Cu(II) under physiological conditions. 279,280…”
Section: Dalton Transactionsmentioning
confidence: 99%
“…It is thus conceivable that PrP Sc or mutant PrPs in neurons might target the intracellular vesicle trafficking system, eventually causing neuronal dysfunctions associated with prion diseases. In this series, Cherry and Gilch reviewed the possible mechanism of the PrP Sc -associated vesicular trafficking defect by highlighting how the Rab GTPase family-associated vesicular trafficking system is impaired in prion-infected neurons [ 17 ]. Alves et al also discussed the mechanism of the inter- and intra-cellular trafficking of PrP C and PrP Sc [ 18 ].…”
mentioning
confidence: 99%